EMPLOYEES’ ADHERENCE TO AN ORGANIZATIONAL OBJECTIVE WITH THE HELP OF COMMITMENT COMMUNICATION ACTS - Nicolas GUÉGUEN; Isabelle GRANJEAN; Sébastien MEINER (Revue de Gestion des Ressources Humaines, 2011)
The aim of this study was to improve organizational communication for employees by using commitment communication methods. Within the framework of a global progress plan, visual communication actions were defined in an aeronautical industry. A commitment communication method was used to contribute to making future communication more effective. Employees were led to realize freely a visible preparatory act (i.e. answer a questionnaire) before the implementation of notice boards and a monthly newsletter. We compared behavioral variables before and after the introduction of these actions. The results indicated that employees more frequently consulted the new available information. Moreover, they significantly enhanced the quality of their work, through the progress of two performance indicators.